Opportunities for Prevention of Complications in Intestinal Stoma Surgery - V. S. Groshilin; V. D. Kuznetsov; D. V. Kuznetsov; A. A. Pogosyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to reduce the number of paracolostomy complications and improve the quality stoma patients’ life by justifying the use of a comprehensive approach to the end colostomy, including preoperative marking, taking into account the variants of the structure of the muscular-aponeurotic frame of the anterior abdominal wall, as well as the individual features of vascularity and topography of the intestine section undergoing ostomy surgery.Materials and methods. To confirm the effectiveness of the proposed algorithm, an analysis of 52 clinical observations in patients who underwent surgeries with the formation of an end colostomy was carried out, which made up two clinical groups. In group 1 (n = 25) the developed therapeutic and diagnostic algorithm was applied, which included a rational choice of the colostomy localization site, taking into account individual features of the anterior abdominal wall structure, the quality of vascularity of the ostomy intestine, the terminal portion of its mesentery, the length and topography of the end section. Group 2 of patients (n = 27) underwent ostomy creation surgery using traditional techniques, without considering individual features.Results. The obtained results indicate the possibility of reducing the number of early (group 1 — 16 %, group 2 — 40.7 %; p < 0.05) and late (group 1 — 8 %, group 2 — 29.6 %; p < 0.05) paracolostomy complications, decreasing the number of repeated surgical interventions (three cases of re-creation of the stoma in the early postoperative period in group 2 and no indication for repeated interventions in group 1) and improving the quality of life in stoma patient through the application of the developed personalized algorithm. The assessment of the psychological (group 1 — 33.24, group 2 — 53.41) and physical (group 1 — 32.46, group 2 — 54.78) components of health based on the results of the SF-36 survey confirmed the advantages of the proposed tactics and therapeutic and diagnostic algorithm in group 1. The average number of hospital-stay days was also less in patients of clinical group 1 — 12.1 ± 3.4 days vs. 16 ± 4.7 in group 2.Conclusions. The use of patient-centered complex approach to determining the place and method of formation of an end colostomy, which includes taking into account the individual structure of the muscular-aponeurotic frame of the anterior abdominal wall, and the peculiarities of vascularity and topography of the intestine section undergoing ostomy surgery, is accompanied by a low number of early and late paracolostomy complications.